The current influence of social media on democratic debate, political parties and electioneering - Fornasier, Mateus de Oliveira; Borges, Gustavo Silveira (Revista de Investigações Constitucionais, 2022)
This article provides an overview on how digital social media influences the debate and some of the major democratic organizations — namely political parties and electioneering campaigns. Its specific objectives are: i) to expose the debate about the democratic essence (or not) of the internet; ii) to analyze risk factors for democracy brought about by the digitization of social communications; iii) to study the transformations brought by the Internet to political parties and electoral campaigns. Results: i) what will define if there will still be the possibility of some democratic degree in the use of the internet will be the predominance of the forces (consumerist or communitarian) that build it; ii) immediacy, lack of moderation, lack of search for conformity and balance, anti-democratic technological strategies and technological colonialism expose the democratic debate to great risks of degradation; iii) participatoryism and disintermediation are ideological features of the new digitized parties that, at heart, hide a centralization around charismatic figures without a stable and fully definable electoral platform. It has a hypothetical-deductive method of procedure, qualitative approach, and bibliographic-documentary research technique.